The Influence of Financial Literacy and Digital Literacy on Crypto Investment Decisions with FOMO as a Moderating Variable - Yusuf Hendri Gunawan; Khresna Bayu Sangka (International Journal of Economics and Management Research, 2025)
This research aims to understand the influence of financial literacy and digital literacy on decision-making in investing in crypto assets, with fear of missing out serving as a moderation variable among the Nakama DAO community. The method used is quantitative research with a survey approach. The research sample consisted of 366 members of the Nakama DAO community who were selected through a simple random sampling technique. Data was collected using questionnaires. Data analysis was carried out through a number of techniques, such as descriptive analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test, determination coefficient test, t-test, and MRA test. The findings of this study show a positive influence between financial literacy and investment decisions in crypto assets, as evidenced by the t-value of the calculation (2.334) which is greater than the t table (1.971) and the significance value of 0.02 which is less than 0.05. It was also found that there was a positive influence between digital literacy and the decision to invest in crypto assets, with a t-count value (2.678) greater than the t-table (1.971) and a significance value of 0.008 which was also less than 0.05. Based on the results of the moderation regression analysis, fear of missing out does not play a moderator role in influencing the relationship between financial literacy and digital literacy and investment decisions in crypto assets. The results of this study are expected to contribute to future researchers in investigating the effects of financial literacy and digital literacy on crypto asset investment decisions with fear of missing out as a moderation variable.